Multinational Andean Project. Report #11 Part”A”: 1998/99 Year end Activity Report. Fourth Quarter Financial Report – 1998/99 - Hickson, Catherine J. (1999)
Multinational Andean Project. Canadian International Development Agency, Arrangement: 24846, RC/Project: 540/20080. Commitment: 189086, Supplier: G41000